1998
DOI: 10.1159/000040826
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Transplantation for Autoimmune Diseases

Abstract: Bone marrow transplantation (BMT) is now becoming a powerful strategy for the treatment of patients with autoimmune diseases. Using various animal models for autoimmune diseases, we have previously found that allogeneic BMT (not autologous BMT) can be used to treat autoimmune diseases such as systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), immune thrombocytic purpura, insulin-dependent diabetes mellitus (IDDM), chronic glomerulonephritis, and certain types of non-insulin-dependent diabetes melli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 31 publications
0
61
0
1
Order By: Relevance
“…Experimental study in animal models has demonstrated that various autoimmune diseases can be transferred to healthy animals by BMT after total body irradiation [17]. Additionally, transfer of other autoimmune diseases has been reported in human BMT [7,18].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental study in animal models has demonstrated that various autoimmune diseases can be transferred to healthy animals by BMT after total body irradiation [17]. Additionally, transfer of other autoimmune diseases has been reported in human BMT [7,18].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to autoimmune diseases could also be transferred to susceptible strains by haematopoietic cells. In mice, HCT from disease-resistant allogeneic animals (allo-HCT) prevented the development of SLE, type 1 diabetes, EAE and other autoimmune diseases 3,4 .…”
Section: Animal Models Provide the Rationale For Hctmentioning
confidence: 99%
“…Therefore this immune reactivity is likely to be a graft-versus-host (GVH) response. Third, animal studies indicate that resistance to autoimmune disease resides in and can be transferred by HSC [2][3][4] . Finally, engraftment of allo-HSC could result in tolerance to donor antigens, permitting acceptance of donor-derived tissue (for example, islets) without chronic immunosuppressive therapy.…”
Section: Immunomodulation By Immunosuppressive Conditioning and Auto-hctmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow transplantation has been widely accepted as a powerful practical strategy in the treatment of life-threatening diseases such as leukemia, anaplastic anemia, and congenital immunodeficiency (Ikehara, 1998(Ikehara, ,2001). Precursor cells derived from bone marrow, which could integrate appropriately in the CNS and remyelinate, would be a potentially important cell candidate for transplantation in demyelinating diseases.…”
Section: Introductionmentioning
confidence: 99%